An Investment Perspective on Global Value Chains - Qiang, Christine Zhenwei; Liu, Yan; Steenbergen, Victor (Washington, DC: World Bank, 2021)
This book examines the role of foreign direct investment (FDI) in global value chains (GVCs). To stimulate economic transformation through GVCs, policy makers in developing countries need to better understand the business strategies of multinational corporations (MNCs), internationalization pathways for domestic firms, and how policies can create a favorable environment for both types of firms. Part I brings together the latest theories and empirical evidence to illustrate the mutually reinforcing relationship between FDI and GVC participation. It argues that MNCs have driven the phenomenal rise of GVCs in the past three decades as they have unbundled production processes and spread their networks on a global scale. Domestic firms benefit considerably from their participation in GVCs as they learn from MNCs through investment, partnerships, or trade. Part II includes six case studies examining the approaches of developing countries to leveraging FDI to stimulate and facilitate GVC participation and upgrading. The cases include Kenya (horticulture), Honduras (apparel), Malaysia (electronics), and Mauritius (tourism). Another case focuses on the digital economy for the Republic of Korea, India, and China. Each case study presents a different approach by which policy makers have leveraged FDI to stimulate and facilitate GVC participation and upgrading. A quantitative case study on Rwanda and West Bengal, India, uses firm- and transaction-level data to provide new insights into the dynamics between MNCs and domestic firms in selected value chains. The report also discusses the recent COVID-19 (coronavirus) pandemic and its potential impact on FDI and GVCs. The outbreak has triggered new questions about GVCs and accelerated precrisis global trends such as digitalization and economic nationalism. How MNCs and their supplier firms respond to the supply and demand shocks as well as policy uncertainties will play a critical role in crisis responses and recovery.